2007
DOI: 10.1111/j.1095-8312.2007.00842.x
|View full text |Cite
|
Sign up to set email alerts
|

Cuttlefish camouflage: a quantitative study of patterning

Abstract: To investigate camouflage design, we compared the responses of two species of cuttlefish (Sepia officinalis and Sepia pharaonis) with controlled but naturalistic backgrounds, consisting of mixtures of 1-mm and 9-mm diameter coloured pebbles. Quantitative analysis of image data using methods adapted from functional imaging research found differences in how the two species camouflage themselves. Whereas S. officinalis switches from background resemblance to a disruptive pattern as it moves from a fine to a coars… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 19 publications
1
25
0
Order By: Relevance
“…Most obviously one can test the effects of varying a specific image parameter in the background. Studies have used both printed patterns, such as checkerboards (Fig 1B;Chaio & Hanlon 2001;Zylinski et al 2009a), and more natural substrates, such as sand, gravel and stones (Marshall & Messenger 1996;Shohet et al 2007;Barbosa et al 2008). Patterns have been designed to test the animals' sensitivity to low-level visual parameters, including colour, spatial frequency, contrast, orientation and spatial phase (Marshall & Messenger 1996, Zylinski & Osorio 2011, or local features such as edges, objects and depth cues (e.g.…”
Section: Cuttlefishmentioning
confidence: 99%
“…Most obviously one can test the effects of varying a specific image parameter in the background. Studies have used both printed patterns, such as checkerboards (Fig 1B;Chaio & Hanlon 2001;Zylinski et al 2009a), and more natural substrates, such as sand, gravel and stones (Marshall & Messenger 1996;Shohet et al 2007;Barbosa et al 2008). Patterns have been designed to test the animals' sensitivity to low-level visual parameters, including colour, spatial frequency, contrast, orientation and spatial phase (Marshall & Messenger 1996, Zylinski & Osorio 2011, or local features such as edges, objects and depth cues (e.g.…”
Section: Cuttlefishmentioning
confidence: 99%
“…Psychophysical experiments have shown that the size of substrate objects can determine which camouflaged body pattern a cuttlefish will show (e.g. Hanlon & Messenger 1988;Chiao & Hanlon 2001a,b;Barbosa et al 2007Barbosa et al , 2008bChiao et al 2007;Mäthger et al 2007;Shohet et al 2007). Large light objects on overall dark backgrounds (e.g.…”
Section: Visual Background Features That Evoke Uniform Mottle and DImentioning
confidence: 99%
“…They identified 34 chromatic components in S. officinalis and classified its body patterns into 13 categories (Hanlon and Messenger, 1988). Because the chromatic components have not been identified in S. pharaonis, we used the repertoire of chromatic components of S. officinalis, which shows body patterns similar to S. pharaonis (Shohet et al, 2007) and shares many chromatic components with it.…”
Section: Discussionmentioning
confidence: 99%